2002
DOI: 10.1161/01.cir.0000044389.51236.91
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Ventricular Thrombi With Contrast-Enhanced Magnetic Resonance Imaging in Patients With Ischemic Heart Disease

Abstract: Background-Ventricular thrombus formation is a frequent and potentially dangerous complication in patients with ischemic heart disease. Although transthoracic echocardiography (TTE) is generally used as diagnostic technique, we explored the role of contrast-enhanced (CE)-MRI to detect ventricular thrombi. Methods and Results-In 57 patients with acute myocardial infarction, chronic myocardial infarction, or ischemic cardiomyopathy, MRI was performed to evaluate ventricular function (CINE-MRI) and to depict pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(137 citation statements)
references
References 12 publications
1
129
0
7
Order By: Relevance
“…Furthermore, late-enhancement MRI may be used in a wider range of pathologies, including intra-cardiac thrombi, cardiomyopathies, myocarditis, cardiac masses and congenital heart disease [11][12][13][14][15]. The findings of the present study suggest that late-enhancement cardiac MRI can also be used to complement 'black-blood' spin-echo MRI in the assessment of the pericardium.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, late-enhancement MRI may be used in a wider range of pathologies, including intra-cardiac thrombi, cardiomyopathies, myocarditis, cardiac masses and congenital heart disease [11][12][13][14][15]. The findings of the present study suggest that late-enhancement cardiac MRI can also be used to complement 'black-blood' spin-echo MRI in the assessment of the pericardium.…”
Section: Discussionmentioning
confidence: 87%
“…Some areas were characterized by a persistent hypoenhanced area surrounded by hyperenhancement, reflecting PMO [13]. PMO was differentiated from mural thrombus by using criteria previously described [14]. PMO areas were visually interpreted as absent or present, and manually traced if present.…”
Section: Cmr Data Analysismentioning
confidence: 99%
“…9). In a recent study by Mollet et al, delayed contrast-enhanced MRI demonstrated significantly more ventricular thrombi in patients with ischemic heart disease than balanced-SSFP cine MRI and echocardiography [28]. This technique is definitely superior to detect small mural thrombi or thrombi trapped in endocardial trabeculations.…”
Section: Imaging Of the Cardiac Cavitiesmentioning
confidence: 96%